Recycling of thermoplastics composites - Lee, Ian Zi Feng (Nanyang Technological University, 2024)
Carbon Fibers (CFs) are commonly used to reinforce polymer matrix composites (PMCs) due to their exceptional properties, including high specific tensile strength, lightweight design, and superior load-bearing capacity at elevated temperatures. This report focuses on Carbon Fiber Reinforced Thermoplastic (CFRTP) because of its recyclability properties. Recycling CFRTP is crucial because an estimated 23,360 tons of Carbon Fiber composite waste will be produced annually until 2035. The CFRTP manufactured in this report used Carbon Fiber (CF) and Polyamide 6 (PA6) to produce pristine CFPA6 laminate composite because of their beneficial properties. The report examines mechanical and chemical recycling methods to ascertain mechanical properties through tensile and flexural testing, conducting fractography studies to comprehend different failure modes, assessing industry feasibility, and analysing costs and future works. For mechanical recycling, compare mechanically recycled CFPA6 composite mechanical properties between recycled CFPA6 composite CF oriented at a 45-degree and 90-degree angle and against pristine CFPA6 laminate composite by tensile testing. Tensile testing showed a significant reduction in mechanically recycled CFPA6 composite average tensile strength, and CFPA6 composite CF oriented at a 45-degree angle has 42.094% better tensile strength than at a 90-degree angle. As for chemical recycling, formic acid was used to successfully recover CF and PA6 from pristine CFPA6 laminate composite. Chemically recycled CFPA6 was manufactured to compare the average maximum flexural stress against pristine CFPA6 laminate composite by flexural tests. Significant improvement in the average maximum flexural stress was observed.